Analisis Pengaruh Perilaku Bullying terhadap Prestasi Akademik Siswa di Sekolah Dasar - Sunanih Sunanih; Arsi Nurhaliza; Amelia Shakila; Desi Nadia Ulpah; Dika Rahmaldi; Dinda Nur Farida; Intan Maulida; Maitsa Ashilah; Nisa Amalia Rahmawati; Reja Firman Saputra; Syiva Nurul Qurani; Wilda Utami; Diana Santi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
His study aims to analyze the impact of bullying behavior on students' academic performance at SDN 1 Cireungit. Using a descriptive qualitative method, data were collected through interviews, observations, and a literature review of five relevant journals. The findings reveal that bullying, both verbal and non-verbal, significantly negatively impacts students. Verbal bullying, such as mockery and insults, is the most prevalent form. Its effects include anxiety, depression, low self-esteem, decreased learning motivation, and difficulty concentrating in class, which collectively contribute to declining academic performance and long-term mental and social development challenges. The school’s response includes forming a Violence Prevention and Handling Team (TPPK) involving all teachers and providing individualized support to victims and perpetrators. However, the program’s effectiveness depends on consistent implementation and the active participation of teachers, students, and parents. This study highlights the importance of holistic bullying prevention strategies, such as creating inclusive learning environments, providing moral education to students, involving parents in recovery processes, and ensuring professional support for victims. The research significantly contributes to the development of collaborative strategies to foster a safe educational environment that supports students' holistic growth.